Cytoplasmic "ciliary inclusions" in isolation are not sufficient for the diagnosis of primary ciliary dyskinesia. - Vece, Timothy J; Sagel, Scott D; Zariwala, Maimoona A; Sullivan, Kelli M; Burns, Kimberlie A; Dutcher, Susan K; Yusupov, Roman; Leigh, Margaret W; Knowles, Michael R (Pediatr Pulmonol, 2020)
BACKGROUND: The diagnosis of primary ciliary dyskinesia (PCD) is difficult and requires a combination of clinical features, nasal nitric oxide testing, cilia ultrastructural analysis by electron microscopy (EM), and genetics. A recently described cytoplasmic ultrastructural change termed "ciliary inclusions" was reported to be diagnostic of PCD; however, no supporting evidence of PCD was provided. In this study, we sought to confirm, or refute, the diagnosis of PCD in subjects with "ciliary inclusions" on EM. METHODS: Six subjects from five families with previous lab reports of "ciliary inclusions" on EMs of ciliated cells were identified and evaluated at a Genetic Disorders of Mucociliary Clearance Consortium site. We performed a detailed clinical history, nasal nitric oxide measurement, genetic testing including whole-exome sequencing (WES), and when possible, repeat ciliary EM study. RESULTS: Only one of six subjects had multiple and persistent clinical features congruent with PCD. No subject had situs inversus. Only one of six subjects had a very low nasal nitric oxide level. No "ciliary inclusions" were found in three subjects who had a repeat ciliary EM, and ciliary axonemal ultrastructures were normal. Genetic testing, including WES, was negative for PCD-causing genes, and for pathogenic variants in gene pathways that might cause "ciliary inclusions," such as ciliary biogenesis. CONCLUSION: "Ciliary Inclusions", in isolation, are not sufficient to diagnosis PCD. If seen, additional studies should be done to pursue an accurate diagnosis.
Keywords: Child, Preschool; Cilia; Ciliary Motility Disorders; Female; Genetic Testing; Humans; Infant; Male; Nasal Mucosa; Nitric Oxide; Whole Exome Sequencing

Identification of genetic variants in CFAP221 as a cause of primary ciliary dyskinesia. - Bustamante-Marin, Ximena M; Shapiro, Adam; Sears, Patrick R; Charng, Wu-Lin; Conrad, Donald F; Leigh, Margaret W; Knowles, Michael R; Ostrowski, Lawrence E; Zariwala, Maimoona A (J Hum Genet, 2020)
Primary ciliary dyskinesia (PCD) is a rare disorder that affects the biogenesis or function of motile cilia resulting in chronic airway disease. PCD is genetically and phenotypically heterogeneous, with causative mutations identified in over 40 genes; however, the genetic basis of many cases is unknown. Using whole-exome sequencing, we identified three affected siblings with clinical symptoms of PCD but normal ciliary structure, carrying compound heterozygous loss-of-function variants in CFAP221. Computational analysis suggests that these variants are the most damaging alleles shared by all three siblings. Nasal epithelial cells from one of the subjects demonstrated slightly reduced beat frequency (16.5 Hz vs 17.7 Hz, p = 0.16); however, waveform analysis revealed that the CFAP221 defective cilia beat in an aberrant circular pattern. These results show that genetic variants in CFAP221 cause PCD and that CFAP221 should be considered a candidate gene in cases where PCD is suspected but cilia structure and beat frequency appear normal.
Keywords: Alleles; Calmodulin-Binding Proteins; Cilia; Ciliary Motility Disorders; Epithelial Cells; Exons; Genetic Variation; Humans; Mutation; Proteins; Whole Exome Sequencing

Mutation of CFAP57, a protein required for the asymmetric targeting of a subset of inner dynein arms in Chlamydomonas, causes primary ciliary dyskinesia. - Bustamante-Marin, Ximena M; Horani, Amjad; Stoyanova, Mihaela; Charng, Wu-Lin; Bottier, Mathieu; Sears, Patrick R; Yin, Wei-Ning; Daniels, Leigh Anne; Bowen, Hailey; Conrad, Donald F; Knowles, Michael R; Ostrowski, Lawrence E; et al. (PLoS Genet, 2020)
Primary ciliary dyskinesia (PCD) is characterized by chronic airway disease, reduced fertility, and randomization of the left/right body axis. It is caused by defects of motile cilia and sperm flagella. We screened a cohort of affected individuals that lack an obvious axonemal defect for pathogenic variants using whole exome capture, next generation sequencing, and bioinformatic analysis assuming an autosomal recessive trait. We identified one subject with an apparently homozygous nonsense variant [(c.1762C>T), p.(Arg588*)] in the uncharacterized CFAP57 gene. Interestingly, the variant results in the skipping of exon 11 (58 amino acids), which may be due to disruption of an exonic splicing enhancer. In normal human nasal epithelial cells, CFAP57 localizes throughout the ciliary axoneme. Nasal cells from the PCD patient express a shorter, mutant version of CFAP57 and the protein is not incorporated into the axoneme. The missing 58 amino acids include portions of WD repeats that may be important for loading onto the intraflagellar transport (IFT) complexes for transport or docking onto the axoneme. A reduced beat frequency and an alteration in ciliary waveform was observed. Knockdown of CFAP57 in human tracheobronchial epithelial cells (hTECs) recapitulates these findings. Phylogenetic analysis showed that CFAP57 is highly conserved in organisms that assemble motile cilia. CFAP57 is allelic with the BOP2/IDA8/FAP57 gene identified previously in Chlamydomonas reinhardtii. Two independent, insertional fap57 Chlamydomonas mutant strains show reduced swimming velocity and altered waveforms. Tandem mass tag (TMT) mass spectroscopy shows that FAP57 is missing, and the "g" inner dyneins (DHC7 and DHC3) and the "d" inner dynein (DHC2) are reduced, but the FAP57 paralog FBB7 is increased. Together, our data identify a homozygous variant in CFAP57 that causes PCD that is likely due to a defect in the inner dynein arm assembly process.
Keywords: 3T3 Cells; Adult; Animals; Axoneme; Cells, Cultured; Chlamydomonas reinhardtii; Cilia; Ciliary Motility Disorders; Codon, Nonsense; Conserved Sequence; Dyneins; Humans; Male; Mice; Microtubule-Associated Proteins; Plant Proteins; Proteins; Respiratory Mucosa

Lack of GAS2L2 Causes PCD by Impairing Cilia Orientation and Mucociliary Clearance. - Bustamante-Marin, Ximena M; Yin, Wei-Ning; Sears, Patrick R; Werner, Michael E; Brotslaw, Eva J; Mitchell, Brian J; Jania, Corey M; Zeman, Kirby L; Rogers, Troy D; Herring, Laura E; Refabért, Luc; Thomas, Lucie; et al. (Am J Hum Genet, 2019)
Primary ciliary dyskinesia (PCD) is a genetic disorder in which impaired ciliary function leads to chronic airway disease. Exome sequencing of a PCD subject identified an apparent homozygous frameshift variant, c.887_890delTAAG (p.Val296Glyfs13), in exon 5; this frameshift introduces a stop codon in amino acid 308 of the growth arrest-specific protein 2-like 2 (GAS2L2). Further genetic screening of unrelated PCD subjects identified a second proband with a compound heterozygous variant carrying the identical frameshift variant and a large deletion (c.867_343+1207del; p.?) starting in exon 5. Both individuals had clinical features of PCD but normal ciliary axoneme structure. In this research, using human nasal cells, mouse models, and X.laevis embryos, we show that GAS2L2 is abundant at the apical surface of ciliated cells, where it localizes with basal bodies, basal feet, rootlets, and actin filaments. Cultured GAS2L2-deficient nasal epithelial cells from one of the affected individuals showed defects in ciliary orientation and had an asynchronous and hyperkinetic (GAS2L2-deficient = 19.8 Hz versus control = 15.8 Hz) ciliary-beat pattern. These results were recapitulated in Gas2l2 mouse tracheal epithelial cell (mTEC) cultures and in X. laevis embryos treated with Gas2l2 morpholinos. In mice, the absence of Gas2l2 caused neonatal death, and the conditional deletion of Gas2l2 impaired mucociliary clearance (MCC) and led to mucus accumulation. These results show that a pathogenic variant in GAS2L2 causes a genetic defect in ciliary orientation and impairs MCC and results in PCD.
Keywords: Animals; Cilia; Ciliary Motility Disorders; Disease Models, Animal; Exons; Female; Gene Deletion; Genes, Lethal; Humans; Male; Mice; Mice, Knockout; Microfilament Proteins; Microtubule-Associated Proteins; Phenotype; Rotation; Xenopus

An siRNA-based functional genomics screen for the identification of regulators of ciliogenesis and ciliopathy genes. - Wheway, Gabrielle; Schmidts, Miriam; Mans, Dorus A; Szymanska, Katarzyna; Nguyen, Thanh-Minh T; Racher, Hilary; Phelps, Ian G; Toedt, Grischa; Kennedy, Julie; Wunderlich, Kirsten A; Sorusch, Nasrin; Abdelhamed, Zakia A; et al. (Nat Cell Biol, 2015)
Defects in primary cilium biogenesis underlie the ciliopathies, a growing group of genetic disorders. We describe a whole-genome siRNA-based reverse genetics screen for defects in biogenesis and/or maintenance of the primary cilium, obtaining a global resource. We identify 112 candidate ciliogenesis and ciliopathy genes, including 44 components of the ubiquitin-proteasome system, 12 G-protein-coupled receptors, and 3 pre-mRNA processing factors (PRPF6, PRPF8 and PRPF31) mutated in autosomal dominant retinitis pigmentosa. The PRPFs localize to the connecting cilium, and PRPF8- and PRPF31-mutated cells have ciliary defects. Combining the screen with exome sequencing data identified recessive mutations in PIBF1, also known as CEP90, and C21orf2, also known as LRRC76, as causes of the ciliopathies Joubert and Jeune syndromes. Biochemical approaches place C21orf2 within key ciliopathy-associated protein modules, offering an explanation for the skeletal and retinal involvement observed in individuals with C21orf2 variants. Our global, unbiased approaches provide insights into ciliogenesis complexity and identify roles for unanticipated pathways in human genetic disease.
Keywords: Abnormalities, Multiple; Animals; Caenorhabditis elegans; Cerebellar Diseases; Cerebellum; Cilia; Ciliary Motility Disorders; Databases, Genetic; Ellis-Van Creveld Syndrome; Eye Abnormalities; Genetic Markers; Genetic Predisposition to Disease; Genetic Testing; Genome-Wide Association Study; Genomics; HEK293 Cells; High-Throughput Nucleotide Sequencing; Humans; Kidney Diseases, Cystic; Membrane Proteins; Mice, Inbred C57BL; Mice, Knockout; Mutation; Phenotype; Photoreceptor Cells; Pregnancy Proteins; Proteins; Reproducibility of Results; Retina; RNA Interference; Suppressor Factors, Immunologic; Transfection; Zebrafish